Nonlinear Creep Behavior and Viscoelastic-Plastic Constitutive Model of Rock-Concrete Composite Mass - Yang Liu; Da Huang; Baoyun Zhao; Chen Wang; Duofeng Cen (Advances in Civil Engineering)
The joint force deformation of rock-concrete composite structures is different from that of simple rock specimens or concrete specimens, such as the tunnel surrounding rock-lining concrete, dam foundations, and concrete. In order to study the creep mechanical properties of rock-concrete composite structures under long-duration load, the TFD-2000 microcomputer servo triaxial creep testing machine is used to carry out step loading creep tests on rock-concrete composite specimens (hereinafter referred to as composite specimens) under different confining pressures (including the confining pressures σ3 = 0 MPa). The creep test results show that, under the same confining pressure, when axial deviatoric stress is applied step-by-step according to 10%, 20%, 30%, 40%, 50%, and so forth of the UCS (σ3 = 0 MPa) and TCS (triaxial compressive strength) of the composite specimens, the failure stress that the specimen can bear is closely related to the confining pressure. When the confining pressures are 0 MPa, 7 MPa, 15 MPa, and 22 MPa, respectively, the failure stresses that the composite specimens can bear are 60% (corresponds to 0 MPa), 50%, 30%, and 20% of the TCS under the current confining pressures, respectively. Under the same confining pressure, the initial creep rate of the composite specimen on each step shows a U-shaped change trend. Meanwhile, the instantaneous creep rate and failure creep rate of the specimen increase as the confining pressure increases. When the failure creep rate is excluded, the initial creep rate of other stepped loads at the same confining pressure level decreases step-by-step. The improved Nishihara model can better describe the whole creep process of rock-concrete composite specimens, especially in the accelerating creep step. The testing data and research results in this paper can serve as references for further research on mechanical properties of rock-concrete composite structures.